Statistical Analysis of Frequency Response Collected on Fault Stator Winding in Three Phase Induction Motor - Witjoanes, Zeachter; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2022)
Electric motors are the most used electrical machines in the industry. The three-phase induction motors (TPIM) are commonly used for conveyors, compressors, elevators, etc. However, TPIM can be prone to a variety of problems that cause motor malfunctions also failures and the most important part is the stator windings. This paper is about using three types of statistical indicators (SIs) such as Correlation Coefficient (CC), Absolute Sum of Logarithmic Error (ASLE), and Root Mean Square Error (RMSE) to detect the frequency response’s deformation on fault stator windings. The data was collected from a previous literature review that used frequency response analysis (FRA) in TPIM with various faults stator windings. This paper aims are to simulate the frequency responses (FRs) using statistical indicators (SIs) and propose a benchmark limit for one of the SI. Thus, the simulated frequency response is compared with the measured frequency response of a normal winding condition and faulty winding motor condition. The proposed method has shown SIs are useful to detect winding deformation in TPIM.